FEEDING TECHNIQUES FOR SALINE TILAPIA NURSERIES (Oreochromis niloticus) IN GAMPONG BLANG PADANG SOUTHWEST ACEH DISTRICT: TEKNIK PEMBERIAN PAKAN PADA PENDEDERAN IKAN NILA SALIN(Oreochromis niloticus) DI GAMPONG BLANG PADANG KABUPATENACEH BARAT DAYA - Nurhatijah; Indah Permata Sari; Kurnia; Putri Fansa Barawas (WISDOM : Jurnal Pengabdian Kepada Masyarakat Wisdom, 2024)
This Community Service Activity aims to provide information to the community in providing and introducing fisheries science with education and applied good and correct feeding processes to villagers who have side jobs in fish farming. Providing understanding to the community to try to start a side business in the field of fish farming and also knowing how to utilize the natural resources available in Blang Padang village. this activity was carried out in Blang Padang Village, Tangan-Tangan District, Southwest Aceh Regency and was accompanied by the village head and village officials. The method of implementing activities begins with the presentation of material directly to the community, field practices that involve the community in its implementation.  The results obtained from this activity show that the community is interested in starting a new business in the field of fish farming.  All communities involved gained knowledge and understanding in calculating the amount of feed and how to feed properly.  Village officials through BUMG will facilitate the community in starting a saline tilapia aquaculture business, either in terms of funding or providing tools and materials that will be needed by new farmers